Audit Fee Differences Between Pre And Post Covid-19 Pandemic - Mukhlis, Muhammad (E-Jurnal Akuntansi, 2024)
This research aims to determine the dynamics of audit fees at listed companies in Indonesia in the post-COVID-19 era. Specifically, this study examines whether there are significant differences in audit fees between the pre-pandemic and post-pandemic periods, taking into account various factors that might influence these fees. This research uses quantitative methods with a comparative approach to analyze differences in audit fees. This research focuses on a sample of public companies listed on the Indonesia Stock Exchange. The research results show that there is no statistically significant difference in audit fees between the pre-pandemic (2017–2019) and post-pandemic (2020–2021) periods. Audit fees did not differ before COVID-19 and after the pandemic due to auditors utilizing technology in carrying out audit procedures, rapid economic recovery, adaptive business strategies, and industry-specific impacts. This research is an empirical insight into the impact of COVID-19 on audit fees in Indonesia. Keywords: Audit Fees; COVID-19; Financial Reporting; Business Conditions; Indonesian Listed Companies